Polyphosphazene and Non‐Catechol‐Based Antibacterial Injectable Hydrogel for Adhesion of Wet Tissues as Wound Dressing - Ni, Zhipeng; Yu, Haojie; Wang, Li; Liu, Xiaowei; Shen, Di; Chen, Xiang; Liu, Jiyang; Wang, Nan; Huang, Yudi; Sheng, Yan (Advanced healthcare materials, 2022)
Wound dressings with excellent adhesiveness, antibacterial, self‐healing, hemostasis properties, and therapeutic effects have great significance for the treatment of acute trauma. So far, numerous mussel‐inspired catechol‐based wet adhesives have been reported, opening a pathway for the treatment of acute trauma. However, catechol‐based hydrogels are easily oxidized, which limits their applications. Here, the design of a polyphosphazene and non‐catechol based antibacterial injectable hydrogel is reported as a multifunctional first aid bandage. Inspired by barnacle cement proteins, a series of dynamic phenylborate ester based adhesive hydrogels are prepared by combining the cation–π structure modified polyphosphazene with polyvinyl alcohol. The inherent antibacterial property (4 h antibacterial rate 99.6 ± 0.2%), anti‐mechanical damage, and hemostatic behavior are investigated to confirm multi‐functions of wound dressings. In water, the hydrogels firmly adhere to tissue surfaces through cation–π and π–π interactions as well as hydrogen bonding (adhesion strength = 45 kPa). Moreover, in vivo experiments indicate the hydrogels can shorten the bleeding time and reduce the amount of bleeding by 88%, and significantly accelerate the wound healing rate. These hydrogels have a promising application in the treatment of acute trauma, which is in urgent need of anti‐infection and hemostasis. Inspired by barnacle cement proteins, a series of dynamic phenylborate ester‐based adhesive hydrogels are prepared by combining the cation–π structure‐modified polyphosphazene with polyvinyl alcohol. The dressings with excellent adhesiveness, antibacterial, self‐healing, hemostasis properties, and therapeutic effects have great significance for the treatment of acute trauma.